Targeted Conservation to Safeguard a Biodiversity Hotspot from Climate and Land-Cover Change - Struebig, Matthew J.; Wilting, Andreas; Gaveau, David L.A; Meijaard, Erik; Smith, Robert J; Faisal Ali, Bin Anwarali Khan; Fischer, Manuela; Metcalfe, Kristian; Kramer-Schadt, Stephanie; The Borneo Mammal Distribution Consortium, [et. al..] (Elsevier Ltd, 2015)
Responses of biodiversity to changes in both land cover and climate are recognized [ 1 ] but still poorly understood [ 2 ]. This poses significant challenges for spatial planning as species could shift, contract, expand, or maintain their range inside or outside protected areas [ 2 , 3 , 4 ]. We examine this problem in Borneo, a global biodiversity hotspot [ 5 ], using spatial prioritization analyses that maximize species conservation under multiple environmental-change forecasts. Climate projections indicate that 11%–36% of Bornean mammal species will lose ≥30% of their habitat by 2080, and suitable ecological conditions will shift upslope for 23%–46%. Deforestation exacerbates this process, increasing the proportion of species facing comparable habitat loss to 30%–49%, a 2-fold increase on historical trends. Accommodating these distributional changes will require conserving land outside existing protected areas, but this may be less than anticipated from models incorporating deforestation alone because some species will colonize high-elevation reserves. Our results demonstrate the increasing importance of upland reserves and that relatively small additions (16,000–28,000 km 2) to the current conservation estate could provide substantial benefits to biodiversity facing changes to land cover and climate. On Borneo, much of this land is under forestry jurisdiction, warranting targeted conservation partnerships to safeguard biodiversity in an era of global change.